AN EXPLORATION OF THE CULTURAL BELIEFS OF THE INDONESIAN AND CHINESE PEOPLE IN RELATION TO THE BUSINESS OF SWALLOW FARMING - Christina Leonardo; Sujoko Efferin; Noviaty Kresna Darmasetiawan (CALYPTRA, 2018)
Abstract - This research is basic research that explores the public's trust in swallow farming business. Swiftlet nest is believed to have many benefits for health. Indonesia is the largest producer of swallow's nest in the world. Almost some of the swallow nest produced is exported abroad, especially to China. The purpose of this study is to discuss the reasons behind the belief that is expected to bring information to many people. So that people are able to think wisely and open in every business especially swiftlet nest business. While the method used by the author is qualitative methods by means of interviews, observation and analysis of documents in order to support the validity of the data. The main objects of the research are breeders, collectors and consumers of Swallow nest. The scope of this research is on cultural beliefs in Swallow farming based on Indonesia and China perpective. On the basis of the findings obtained during the study, researchers found that not all swallow nest businessmen believed in the belief. some of them might believe the impact of Swallow farming business but based on different reasons. It has been found not only from the Indonesian perpective but also in Chinese perpective.